HAUNTOLOGICAL HIPO-UTOPIAS: THE UNCANNY AND THE SLOW CANCELLATION OF THE FUTURE IN LATIN AMERICAN DYSTOPIAN CINEMA (INSÓLITA - Revista Brasileira de Estudos Interdisciplinares do Insólito, da Fantasia e do Imaginário, 2026)
Based on Franco Berardi's diagnoses of the "slow cancellation of the future" and Mark Fisher's observations on the blocking of horizons imposed by "capitalist realism", this study investigates how these cultural conditions manifest in the representation of the future in Latin American dystopian cinema. To this end, a film corpus composed of Branco Sai, Preto Fica, O Último Azul and El Eternauta is analyzed. Wilson Ferreira's theory of "hypo-utopia" is articulated with Fisher's perspective on "hauntology" to investigate how dystopian tropes are mobilized allegorically, producing what the article calls "territorial estrangement" – fictional deterritorializations that refer to violent historical events in Latin America, in a hauntological operation where the past haunts the imagination of the future. Finally, it examines how the insertion of the unusual into dystopian reality – in approximation to magical realism – can trace heterotopic breaches that reopen futurability. Keywords: cinema; hipo-utopia; hauntology; uncanny; territorial estrangements.